Morphology, abundance and the invasiveness of coral-killing sponge Chalinula nematifera (Porifera: Demosponigiae) from Con Dao National Park, Vietnam - Quang, Thai Minh (Vietnam Journal of Marine Science and Technology, 2021)
This is the first study on morphology, abundance and invasion of coral-killing sponge Chalinula nematifera (De Laubenfels, 1954) from offshore waters in Con Dao islands, Vietnam. The results of the study show that the morphology is similar to that in the Western Pacific, but differs in skeletal structure compared to the description in the Eastern Pacific. The density of C. nematifera (average ± standard deviation) is 2.02 ± 5.03 colonies per 100 m2 (present at 12/15 survey stations) with the number of colonization belonging to diameter group 5–20 cm. They invade 30 species belonging to 23 genera of Scleractinia corals (44.7% on foliose/laminar and encrusting coral, 23.86% on massive coral and 21.97% on branching coral). The ability to invade corals of C. nematifera does not limit the host. So, this is considered a potential hazard to the East Vietnam Sea coral reefs in the future